Design of an attachable MIDI keyboard - Wang, Ziyin. (2013)
MIDI is the acronym for Musical Instrument Digital Interface. A MIDI keyboard is typically a piano-style user interface keyboard device used for sending MIDI signals or commands over a USB or MIDI cable to other devices connected and operating on the same MIDI protocol interface. With a history of 30 years, MIDI keyboards are now a very common feature of a recording studio, digital audio workstations as well as live music performances. Recent development of MIDI devices shows a trend in reduction of weight and size and increase of portability. This project aims at creating a novel design of MIDI keyboard consisting of small modules, which can be easily taken apart and transported, then be assembled together. Each module is attached to another by magnets. In this report, detailed designs of the keys and the joining interface are presented. Prototypes are also made for proof of concept and for reference to future development.